(3cJGH aj GdTYQ hGdHdGZIs
(3ChdgG (B:s
(3Chd GdehLhO efg bhdg (B: (3HGH ai CTYGQ GdNdaGA hGdfbdI hGdabgGA ef Pdc bhd CHj HcQ GdUOjb QVi Gddg Yfg bGdhG hESeg YHO Gddg GHf YKeGf s
(3BNQgG (B:s
(3BNQ GdehLhO efg CKfGA HGH GdhUa Hbhd cTGLe ef bUjOI PcQ ajgG WGhhSkG eGJ dg (B: (3hQRjJg QhVI JQhb hde GSeY HQhV jSYi Ydi GdbOe s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3dYdg eNWhW GdYeOg dGHf QTjb s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs